Imagining the State through Digital Technologies: A Case of State-Level Computerization In the Indian Public Distribution System - Silvia Masiero (London School of Economics and Political Science, 2014)
The theory on which the thesis is developed views technology as embedded in its socio- political context, and conceives e-governance as implicated in the reconstruction of images of the state. This vision is applied to the computerization of the main food security programme in India, the Public Distribution System (PDS), as it has been devised and implemented in the state of Kerala. Through an interpretive case study of the object at the core of computerization, known as the Electronic Public Distribution System or e-PDS, the thesis investigates the ICT-led processes of image construction by the state, and the ways in which citizens, confronted with new images, structure their perception of these. Through inclusion of front-end PDS services in existing infrastructure, and through the inscription of a clear problem-solution nexus in e-PDS, the state is found, as expected, to be using e-governance as a means to reconstruct its own image. At the same time, though, the loci of image formation that are found in citizens (direct experience, social networks, and political circuits) systematically escape control by governmental action, and seem to be, in fact, only marginally touched by the ICT-induced reinvention of governance. The thesis results, therefore, in an extension of existing theory in this respect: the capability of the state to reconstruct its image, through the usage of new technologies, is limited by the spaces of image formation which citizens experience in their daily lives.